Study the Effectiveness of the Compensation Management on the Successful of the Private Insurance Company in Jordan (Global Journal of Management and Business Research, 2022)
Abstract not found
Keywords: compensation management; employee satisfaction; effectiveness; performance; benefits; rewards; compensations elements